(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The real estate sector is extremely relevant for the economy our country. In light of the promise made by the government to ensure that housing facilities shall be made available to the public, the enactment of the Real Estate (Regulation and Development) Act, 2016 was more of anecessity than a matter of convenience. The real estate sector was largely an unregulatedsector where the buyer in the market facing extreme inconveniences due to the harshdemands of the builders and the developers. The harshness of the demands was faced more bythe middle income and low income sectors who neither had the liquidity requirements to meetthe demands of the buildersdevelopers nor the knowledge of real estate sector. This paper attempts to highlight the effect of rera on whole real estate sector and gives general idea about how advantageous of the act by analyzing the construction work done with rera act and wi thout rera act. This paper discusses the effect of rera on delays, cost, possession policies and amenities to regulate the construction work in effective system.